AN ANALYSIS OF LECTURERS’ METACOGNITIVE LEARNING STRATEGIES IN TEACHING ENGLISH FOR YOUNG LEARNER AT ENGLISH EDUCATION PROGRAM OF MUHAMMADIYAH UNIVERSITY OF BENGKULU - Dwi Uswatun K; Ria Anggraini; Fetriani; Ivan Achmad N,; Eki Saputra (LPPM STKIP AL MAKSUM, 2020)
The purpose of this reseach was to analyze the lecturers' metacognitive learning strategies in teaching English for young learner at English Education Program of Muhammadiyah University of Bengkulu Academic year 2018/2019. The designof the research used descriptive qualitative method. The objects of this research were 60 students with open questionnaire. The instrument was check list form about metacognitive strategies skills by Anderson and Krathwohl. The researcher found that although not fully applied, with this metacognitive strategy students are more independent in learning and lecturers do not provide material repeatedly.The lecturers should consider several teaching strategies, especially metacognitive strategies.